Population genomic analysis reveals genetic divergence and adaptation in Brachymystax lenok - Li, Ping; Niu, Le; Chang, Jianbo; Kou, Xiaomei; Wang, Wentian; Hu, Wenjing; Liu, Qigen (Frontiers in Genetics, 2024)
Studying how populations in various environments differ genetically is crucial for gaining insights into the evolution of biodiversity. In order to pinpoint potential indicators of divergence and adaptation to diverse environments, we conducted a comprehensive analysis of 3,491,868 single nucleotide polymorphisms (SNPs) derived from five populations of Brachymystax lenok. We discovered significant geographic divergence among these 5 populations, which lack evidence of gene flow among them. Our results further demonstrated that the current distribution pattern of B. lenok are driven by geographical isolation and changes in oceans and rivers. We also performed genome-wide scan and identified the genes evolved to adapt the different environments, including stress response.In general, these results provide genomic support for high-level genetic divergence and the genetic basis of adaptation to different environments.